Outcome and impact assessment in the comprehensive evaluation of rural ICT projects in developing countries - Mthoko, Hafeni Tulimewawa Wilhelmina Lyatenda (Rhodes University, Faculty of Commerce, Department of Information Systems, 2017)
Despite existing literature that indicates that Information and communication technologies (ICTs) act as tools for social change and development, there is still limited empirical evidence that demonstrates this. An outcome and impact assessment based on a comprehensive (holistic) evaluation is deemed appropriate at a time when many ICT4D programmes fail to effectively demonstrate their impact towards rural development. A comprehensive evaluation is one that incorporates the evaluation of the need, design, implementation, outcome and impact, efficiency, and scalability of a programme. These stages make up the different domains of an evaluation lifecycle. The following study aims to develop an outcome and impact assessment framework for ICT4D programmes. It forms part of continuous research associated with the development of a rural ICT Comprehensive Evaluation framework. A theoretical approach, using Design Science and Weick's theorizing process, was applied to investigate the development of a framework (design artefact) for outcome and impact assessment of ICT4D programmes. The theorizing process analysed existing outcome and impact assessment frameworks from social programmes, information systems/technology programmes, and ICT4D programmes. The output of the theorizing process proposes five critical themes of outcome and impact assessment of rural ICT4D programmes that should be assessed. These themes include: Strategic Value, Most Significant Change, Empowerment, Livelihoods, and Sustainability. To assess its utility, the framework was implemented in the Siyakhula Living Lab and Information and Communication Technology for Rural Education (ICT4RED) projects in South Africa. Through the application of the framework in real life ICT4D contexts, the lessons learned contributed to its revision and enhancement. The proposed framework aims to guide evaluators through the assessment of outcomes and impacts in ICT4D programmes. It provides a foundation and justification for the selected outcome and impact assessment themes that contribute to a comprehensive evaluation. An outcome and impact assessment that is informed by: baseline; needs assessment; programme theory assessment; and process assessment data, provides ICT4D evaluators and project stakeholders with meaningful outcome and impact feedback. Having such an approach to outcome and impact assessment ensures that the evaluation process is seen more holistically as part of the ICT4D project as a whole.
Keywords: Rural development projects -- Developing countries; Information and communication technologies for development; Information technology -- Developing countries; Impact assessment; ICT4RED